2005
DOI: 10.1021/jp044798a
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and Infrared Photodissociation of Si+(C6H6)nand Si+(C6H6)nAr Clusters

Abstract: Ion-molecule complexes of the form Si(+)(C6H6)n and Si(+)(C6H6)(n)Ar are produced by laser vaporization in a pulsed nozzle cluster source. These clusters are mass-selected and studied with ultraviolet (355 nm) photodissociation and resonance-enhanced infrared photodissociation spectroscopy in the C-H stretch region of benzene. In the UV, Si(+)(C6H6)n clusters (n = 1-5) fragment to produce the Si(+)(C6H6)n mono-ligand species, suggesting that this ion has enhanced relative stability. IR photodissociation of Si(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 97 publications
1
11
1
Order By: Relevance
“…Interestingly, the η 2 coordination mode was also found in the case of [FePAH] 0 complexes (Simon & Joblin 2007) and [CuPAH] + complexes (Dunbar 2002), and the η 3 coordination mode in the case of [SiPAH] 0/+ , with respect to the most stable dissociation products (Si( 3 P) + PAH) and (Si( 3 P) + PAH + ) (corresponding to ΔH(0 K)) and with respect to (Si + ( 2 P) + PAH) (corresponding to ΔH (0 K)) at the B3LYP/D95++** level of theory. (Jaeger et al 2005). These coordination modes imply both a curvature of the edge of the C-skeleton and ring distortions, which had been already observed in the case of [TM-C 6 H 6 ] + (TM: transition metals) calculated structures (Jaeger et al 2004).…”
Section: Thermodynamics and Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the η 2 coordination mode was also found in the case of [FePAH] 0 complexes (Simon & Joblin 2007) and [CuPAH] + complexes (Dunbar 2002), and the η 3 coordination mode in the case of [SiPAH] 0/+ , with respect to the most stable dissociation products (Si( 3 P) + PAH) and (Si( 3 P) + PAH + ) (corresponding to ΔH(0 K)) and with respect to (Si + ( 2 P) + PAH) (corresponding to ΔH (0 K)) at the B3LYP/D95++** level of theory. (Jaeger et al 2005). These coordination modes imply both a curvature of the edge of the C-skeleton and ring distortions, which had been already observed in the case of [TM-C 6 H 6 ] + (TM: transition metals) calculated structures (Jaeger et al 2004).…”
Section: Thermodynamics and Structuresmentioning
confidence: 99%
“…Srinivas et al (1992) and Jaeger et al (2005) demonstrated theoretically and experimentally that the π-system complex [SiC 6 H 6 ] + is more stable than all the other isomers. Experimental studies on [SiPAH] + complexes are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…1 Up to now, a lot of institutes and universities have studied photochemical properties of organic compounds, such as photodissociation and photocatalytic activities of organic compounds. [2][3][4][5][6][7][8][9][10][11][12][13] Nowadays, photocatalysis is a rapidly expanding technology for wastewater treatment. The photocatalytic degradation process of organic compounds has several advantages such as complete mineralization, nonexistent waste disposal problem, low cost, mild temperature conditions, and mild pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It is of primary interest in cluster research as it yields insight into the energy flow and fragmentation mechanisms of photoexcited cluster ions. 1 In particular, when a cluster includes diatomic ion as a chromophore, photoexcitation can bring about fission of the chromophore into two atomic units which are solvated subsequently.…”
Section: Introductionmentioning
confidence: 99%